Implementasi Qiyas dalam Kehidupan Sehari–Hari - Azhari, Wildan Habib; Tanjung, Dhiauddin (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This article aims to observe and examine the implementation of Qiyas in everyday life, considering that Qiyas is quite important because it is one of the foundations for establishing Islamic law. The main issue discussed is what Qiyas is, and the extent of the urgency of implementing Qiyas in everyday life. This paper is included in research that uses library methods, because it involves a series of activities related to collecting data from written sources, reading, recording, and analyzing research materials. The results of this research conclude that Qiyas is an important component in establishing Islamic law, which will serve as a guide for its application in existance life.